2023
DOI: 10.1186/s13613-023-01116-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous vitamin C monotherapy in critically ill patients: a systematic review and meta-analysis of randomized controlled trials with trial sequential analysis

Abstract: Background A recent landmark randomized controlled trial (RCT) in septic patients demonstrated an increased risk of death and persistent organ dysfunction with intravenous Vitamin C (IVVC) monotherapy, which represents a disparate result from previous systematic reviews and meta-analyses (SRMA). We performed an updated SRMA of IVVC monotherapy to summarize and explore heterogeneity across current trials and conduct trial sequential analysis (TSA) to guard against type-I or type-II statistical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Further analysis of the Sequential Organ Failure Assessment score, inflammatory biomarkers, hypoglycemia, stage 3 acute kidney injury, 6‐month survival, health‐related quality of life, or safety outcomes showed no significant difference between the study intervention and placebo groups. In addition to a meta‐analysis by the LOVIT investigators 6 , another updated meta‐analysis including the LOVIT study still indicated a survival benefit, particularly in those patients with higher degree of mortaility 7 . Taken together, existing evidence including the results of the LOVIT trial indicates that the role of vitamin C in patients with sepsis is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of the Sequential Organ Failure Assessment score, inflammatory biomarkers, hypoglycemia, stage 3 acute kidney injury, 6‐month survival, health‐related quality of life, or safety outcomes showed no significant difference between the study intervention and placebo groups. In addition to a meta‐analysis by the LOVIT investigators 6 , another updated meta‐analysis including the LOVIT study still indicated a survival benefit, particularly in those patients with higher degree of mortaility 7 . Taken together, existing evidence including the results of the LOVIT trial indicates that the role of vitamin C in patients with sepsis is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are comparable to those of other recently published systematic reviews. Three of recent systematic reviews showed reduction in overall mortality with vitamin C mono‐ or combination‐therapy, but certainty of evidence was evaluated as very low, 6 low, 2 or moderate 4 . Other studies did not find firm evidence for a difference in mortality 1,3,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Given its antioxidant properties, researchers hypothesize that vitamin C may attenuate the systemic response to infection that results in organ failure and poor patient outcomes in sepsis. Few interventions in the critically ill population have gained as much attention as vitamin C, with at least six systematic reviews published during the last year alone 1–6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the authors suggested harmful effects, whereas the respective analyzed data (five RCTs, 1722 patients) did not support this finding [28 ▪▪ ]. Most recently, Lee et al published their SRMA with 16 RCTs (2130 patients), including the RCTs mentioned above [29 ▪▪ ]. They showed a significantly reduced overall mortality in patients receiving vitamin C monotherapy.…”
Section: Metaanalysesmentioning
confidence: 98%